“La gestión del inventario y su incidencia en la rentabilidad de la librería “Americana”, ciudad de Riobamba, período 2015”. - Jiménez Guevara, Lilia Maribel (2017)
The investigation entitled "INVENTORY MANAGEMENT AND ITS INCIDENCE IN THE PROFITABILITY OF THE AMERICAN LIBRARY", RIOBAMBA CITY, PERIOD 2015, was developed with the purpose of improving the management of inventories, contributing with results that allow us to know the real value of The investment and the exact quantity of merchandise available for the sale of the company during the study period for the development of the work required a diagnosis of the current situation of the company to proceed with the search of the theoretical information about the Objectives of study the same that was obtained from books, study texts, physical and virtual documents. The methodology used is in inductive because a hypothesis was established starting from the generalities on the management and control of the inventory. The type of research was descriptive and historical because it reports the profitability during a year, as far as its design was the documentary and of field by which it went to the company to observe financial documents and the procedures used. Regarding the population, it was integrated to the proprietary manager, the accountant and employees that the winery has under its responsibility. The interviews determine the opinion of employees of the same that is analyzed by comments issued by the researcher. These results together with the analysis of the initial statement of operations and the income statement for the period provide the guidelines for the preparation of the conclusions and recommendations as a contribution to the improvement of the management of the inventory that was obtained from the company's investigative process.